Pregnancy rate in ewes injected with zinc oxide during an estrus synchronization protocol: Fertility in ewes injected with zinc oxide during a synchronization protocol (Agro Productividad, 2021)
Objective: To measure the effect of zin injection, during an estrus synchronization protocol, on pregnancy rate in sheep from the “Valle de Mexicali”.Design/methodology/approach: The experimental units were 157 ewes, which wereallocated in five farms (UP): UP1 (n=19), UP2 (n=27) UP3 (n=20) UP4 (n=71) and UP5(n=21). In each farm, the ewes were randomly assigned to one of three treatments:control, z-100 and z-200. The ewes from control groups were subcutaneously injectedwith 4 mL of olive oil as placebo. The ewes from groups z-100 and z-200 weresubcutaneously injected with 100 and 200 mg of zinc oxide. The response variableswere the preovulatory diameter of the largest follicle and pregnancy rate.Results: The differences between experimental groups on diameter of the largestpreovulatory follicle and pregnancy rates were not significant different (p>0.05).Limitations of the study/implications: The ewe’s reproductive response to zincinjection might be affected by the animal mineral status, it is recommended to carry onsupplementation with base on mineral blood concentrations.Conclusion: The subcutaneous injection with 100 or 200 mg of zinc oxide did not affectthe size of the largest preovulatory follicle and pregnancy rate in ewes.